An overview of Millionschikov`s quasi-normality hypothesis applied to turbulence - Mamaloukas, ?Christos; Mazumdar, Himadri Pai (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we examine the zero-fourth cumulant approximation that was applied to fluctuating velocity components of homogeneous and isotropic turbulence by M.D. Millionschikov. Since the publication of the remarkable paper of Millionschikov, many authors have applied this hypothesis to solve the closure problem of turbulence.
Keywords: Millionschikov`s quasi-normality hypothesis; homogeneous turbulence; isotropic turbulence; correlation tensors; zero-fourth cumulant approximation